Effects of situational variables on the physical activity profiles of elite soccer players in different score line states - Redwood-Brown, A. J.; O'Donoghue, P. G.; Nevill, A. M.; Saward, C.; Dyer, N.; Sunderland, C. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The aims of this study were to investigate the effects of playing position, pitch location, team ability and opposition ability on the physical activity profiles of English premier league soccer players in difference score line states. A validated automatic tracking system (Venatrack Ltd.) was used to track players in real time (at 25Hz) for total distance covered, high speed running distance and sprint distance. This is the first study to include every team from an entire season in the English premier league, resulting in 376 games, 570 players and 35'000 rows of data from the 2011-12 season being analysed using multi-level modelling. Multi-level regression revealed an inverted "u" shaped association between total distance covered and goal difference (GD), with greater distances covered when GD was zero and reduced distances when GD was either positive or negative. A similar "u" shaped association was found with high speed distance covered at home. In addition distance covered (both at home and away) were predicted by playing position. All activity profiles (with the exception of sprint distance at home) were predicted by pitch location and time scored. Lastly, distance away from home and high speed running at home were predicted by opposition ability. Score line appears to effect player activity profiles across a number of temporal factors and thus should be considered by managers when preparing and selecting teams in order to maximise performance. The current study also highlighted the need for more sensitive score line definitions in which to consider score line effects.